Circumstances of the First Drink among Problem Drinkers Seeking Help from a Psychiatric Service of a Teaching Institute In Eastern Nepal - Shakya, Dhana Ratna (Health Renaissance, 2016)
Background: Alcohol use and problem are common in Nepal. Objective: To investigate into the circumstances of alcohol use among problem drinkers, focusing mainly the first drink. Methods: It is a descriptive study among total of 200 consecutive consenting patients: 100 male and 100 female (gender balance emphasized), with alcohol use disorders seeking help from psychiatric service of a teaching institute in eastern Nepal in 2006-08. Alcohol use disorders were diagnosed with the ‘International classification of diseases and infirmities’ (ICD)- 10th edition. Related information about socio-demography and circumstances of alcohol use were collected by using a ‘semi-structured proforma’ Results: Average (minimum, maximum) age of the subjects was 39.29 (17, 84) years. The age at the first drink was 17.31 (infancy, 59) years: 15.96 (infancy, 45) for males and 18.68 (infancy, 59) for females. As a whole, the most common circumstances of first use were custom of using alcoholic beverage as food, peer pressure/company, stressful situation and easily available at home. Custom of using alcohol as food, stressful situation, making in home and for health reason like during breast feeding were most common circumstances for first drink among females; and peer pressure and the custom were among males. A perceived stressor was associated more among females. Conclusion: Most problem-drinkers first drink in the pretext of the custom of alcoholic beverage as food, peer pressure, stressful situation and easy availability in eastern Nepal. Males start drinking at younger age and the first drink was more associated with stressors among females. Health Renaissance 2014;12(3): 154-161